Plog’s and Butler’s Models: a critical review of Psychographic Tourist Typology and the Tourist Area Life Cycle - Piuchan, Manisa (Turizam, 2018)
This paper attempts to examine the two popular cited theories in tourism studies, Psychographic Tourist Typology by Stanley Plog and the Tourism Area Life Cycles (TALC) by Richard Butler, which have been widely accepted and applied by scholars worldwide and have retained their relevance more than three decades as the pioneer concepts in Tourism. By capturing and reviewing scholarly articles, this paper identifies some key absent issues that should be concerned when use theories in future tourism research.